2006
DOI: 10.1099/mic.0.29083-0
|View full text |Cite
|
Sign up to set email alerts
|

C terminus of NisI provides specificity to nisin

Abstract: Nisin-producing Lactococcus lactis protects its own cell membrane against the bacteriocin with the ABC transporter NisFEG, and the immunity lipoprotein NisI. In this study, in order to localize a site for specific nisin interaction in NisI, a C-terminal deletion series of NisI was constructed, and the C-terminally truncated NisI proteins were expressed in L. lactis. The shortest deletion (5 aa) decreased the nisin immunity capacity considerably in the nisin-negative strain MG1614, resulting in approximately 78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 32 publications
3
46
2
Order By: Relevance
“…For example, NukH, a protein involved in immunity to nukacin ISK-1, is a membrane protein with three transmembrane domains, and its N terminus is located on the cytoplasmic side (31). On the other hand, NisI is a lipoprotein anchored to the extracellular side of the membrane by its N-terminal lipid (39).…”
mentioning
confidence: 99%
“…For example, NukH, a protein involved in immunity to nukacin ISK-1, is a membrane protein with three transmembrane domains, and its N terminus is located on the cytoplasmic side (31). On the other hand, NisI is a lipoprotein anchored to the extracellular side of the membrane by its N-terminal lipid (39).…”
mentioning
confidence: 99%
“…NisI, which is negatively charged (the pI of pre-NisI is 5.2, and the pI of mature NisI is 5.04), interacts with cationic nisin to protect the producing cells. This interaction was proposed to involve both charge-charge interactions and sequence-specific interactions (30). In the case of anionic subtilosin A, the putative immunity peptide AlbB is likely membrane anchored and positively charged (the pI is 10.8); thus, AlbB might interact with subtilosin A, partly based on the opposite charge of the two peptides.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that NisI intercepts nisin before the latter attacks the cell membrane, thereby preventing pore formation. In addition, experiments using C-terminally truncated NisI mutants and a hybrid protein containing an immunity lipoprotein for subtilin (SpaI) have shown that the C terminus of NisI confers protection specifically against nisin (32). However, the details of the substrate-binding mechanism of NisI have not yet been explained.…”
mentioning
confidence: 99%
“…LanFEG is an ATP-binding cassette (ABC) transporter, which mediates the transport of lantibiotics from the cell membrane to the extracellular space (1,4,6,10,22,23,25,28,29). On the other hand, LanI is an immunity lipoprotein anchored to the membrane surface via a lipidmodified N-terminal cysteine residue (4,11,12,16,(27)(28)(29)32). One of the well-studied LanI proteins is NisI, which is involved in nisin immunity.…”
mentioning
confidence: 99%